Can alternative anatomical sites and environmental surveillance replace perianal screening for multidrug-resistant organisms in nursing homes?. (21st August 2022) - Gontjes, Kyle J.; Gibson, Kristen E.; Lansing, Bonnie; Cassone, Marco; Mody, Lona
Abstract: Perianal screening can be intrusive. The sensitivities of multianatomical, nonperianal surveillance were 92.3% for methicillin-resistant Staphylococcus aureus (MRSA), 58.7% for vancomycin-resistant enterococci (VRE), and 54.9% for resistant Gram-negative bacilli (R-GNB). Sensitivities improved upon adding environmental surveillance (95.5%, 82.9%, and 67.9%, respectively). Multianatomical, nonperianal screening and room environment surveillance may replace perianal screening and reduce healthy participant bias in nursing homes.